Cesarean scar dehiscence in early puerperium and influence of barbed suture: tridimensional ultrasound evaluation in a randomized clinical study - Newton de Paula Ishikawa; Gabriela Ewerling Souza; Thays Andressa Albuquerque Monteiro; Albert Schiaveto de Souza; Ricardo Dutra Aydos; Durval Batista Palhares (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: This study investigated the hypothesis of early dehiscence of hysterorrhaphy as the initial stage of post-cesarean uterine scar defects, examining the possible influence of barbed suture in this process. Methods: This longitudinal, prospective, double-blind study included 54 pregnant women with no history of cesarean section, randomized into two suture groups: #0 polyglactin or #1 barbed PDS threads. Sutures were continuous, unlocked, involved the entire myometrium in a single layer, and included the endometrium. Tridimensional transvaginal ultrasonography was performed on the second day postpartum to investigate scar dehiscence and measure its maximal width. Results: The groups had 29 and 25 participants, respectively. Ages: 18–37 (mean 25.80 ± standard error of the mean 0.69) years old. Groups were homogeneous for labor duration, cervical thickness, edge-to-os distance, retroversion, amniotic sac rupture, and additional hemostatic sutures required. Uterine retroversion accounted for 7.4% of cases. Dehiscence was observed in 68.5% (3.98 ± 0.57 mm). The only factor correlating (positively) with dehiscence width was myometrial thickness, whether proximal or distal. Conclusions: Suture type had no influence on early dehiscence, which occurred at the same rate as published niche formation rates. Tridimensional ultrasound proved effective for evaluating dehiscence.